(untitled) (Pedagogy of Higher and Secondary Education, 2004)
The problem of improvement of students with insignificant declanation in the state of health moving activity is considered in the article by Isayeva “Problems of improvement of students’ with some declanation in the state of health moving activity”. The author suggests some trends of process of physical